A cross-sectional study on the prevalence of nomophobia and its impacts on quality of life among medical students in Shimoga, Karnataka - O. P. K., Aseeba; N., Praveen Kumar; M., Chandana (International Journal Of Community Medicine And Public Health, 2024)
Background: Nomophobia refers to discomfort, anxiety, nervousness, or anguish caused by being out of contact with a mobile phone. The highest smartphone penetration was seen among 18–24-year-olds. Recent research indicates that nomophobia is universally present, but the evidence of its effect on the quality of life of potentially vulnerable populations like medical students is less. This study was conducted to estimate the prevalence of nomophobia and to assess its impact on the quality of life of medical students. Methods: A cross-sectional study was conducted among undergraduate medical students who were selected randomly. Nomophobia and quality of life were assessed using NMP-Q and SF 36 questionnaires, respectively. Results: The study comprised 250 medical students. Prevalence of nomophobia was as follows- mild (11.2%), moderate (69.6%), and severe (18.8%). There was a negative correlation between nomophobia and the following domains of quality of life- role of limitation due to emotional problems (r=-0.280, p<0.001), energy/fatigue (r=-0.296, p<0.001), pain (r=-0.232, p<0.001), social functioning (r=-0.263, p<0.001) and emotional well-being (r=-0.316, p<0.001). Conclusions: There is a high prevalence of moderate nomophobia with a negative impact on the multiple physical and emotional domains of the quality of life of medical students.